Cumulative Energy Demand Analysis of Commercial and Hybrid Metal-Composite Gears at Different End-of-Life Strategies - Francesco Borda; Rocco Adduci; Domenico Mundo; Francesco Gagliardi (Journal of Manufacturing and Materials Processing)
Gears remain a fundamental component in mechanical power transmission, with ongoing research focused on enhancing performance and sustainability. This study addresses the process of gear lightweighting, a key factor for efficiency improvements in automotive and aerospace sectors. Traditionally, material removal from gear bodies results in weight reduction, but at the cost of increased noise and vibration. A novel approach using hybrid gears, which combine a metal rim and hub with a composite material web, offers a promising solution. This research proposes a comparative environmental analysis among a conventional full steel, a lightweight and a hybrid gear using a life cycle energy quantification. The study considers two End-of-Life (EoL) scenarios: a conventional open loop scenario with partial recycling and a closed loop scenario with comprehensive recycling, including a thermal recycling for carbon fiber-reinforced plastics. The Cumulative Energy Demand (CED) has been conducted by applying a cradle-to-grave approach. The CED has been evaluated for each gear configuration quantifying the impact of each unit process involved in the production of the gear, from raw material extraction to product manufacturing and from use phase to different EoL scenarios. The cumulative results, performed preserving the same mechanical performance, indicate that the CED of the hybrid gear in the conventional open loop scenario is comparable to the one of the full gears, with an increase of 12.58%. In contrast, in the closed loop scenario, the hybrid gear exhibits substantial energy recovery benefits, with an overall CED difference of 7.50% compared to the lightweight gear and of 28.82% compared to the full gear. These results underline the potential of hybrid gears to improve efficiency, being able to achieve a 20% weight reduction with respect to the full gears, and to reduce environmental impact if effective recycling strategies were implemented.